Degradation kinetics and protein intestinal digestibility of tomato pomace in goats - Long, Yong; Paengkoum, Siwaporn; Lu, Shengyong; Niu, Xinran; Thongpea, Sorasak; Taethaisong, Nittaya; Han, Yong; Paengkoum, Pramote (Frontiers in Veterinary Science, 2026)
IntroductionThis study aimed to analyze and compare the degradation kinetics and intestinal protein digestibility of soybean meal (SBM), whole tomato (WT), and tomato pomace (TP) in the rumen of goats.MethodsThree Boer goats were fitted with permanent rumen cannulas, and all samples were incubated in situ in the rumen for 2, 4, 8, 12, 24, 48, and 72 h using the nylon bag technique. Six nylon bags were prepared for each ruminally cannulated goat in each period (n = 6), resulting in a total of 18 nylon bags for the three goats. Additionally, the samples prepared in the same way were removed following 16 h of in situ incubation in the rumen, the in vitro three-step procedure was used to analyze intestinal protein digestibility.ResultsThe results showed that the degradation rates of dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF), and acid detergent fiber (ADF), as well as the effective degradability (ED) and a* values in WT were higher (P < 0.01) than those in SBM. Moreover, the degradation rates of DM and OM in TP were higher (P < 0.01) than those in SBM (except at 72h of incubation), whereas CP degradation in TP surpassed that of SBM (P < 0.01) only following 8 h of incubation. Finally, the small intestinal digestibility of CP (Idg, %) and small intestine digests CP (IDCP, g/kg) of WT and TP were higher (P < 0.01) than those of SBM.ConclusionWT and TP exhibit a higher degradation rate in the rumen and better protein digestibility in the intestine.